The Effect of Body Balance and Leg Muscle Strength on the Game of Coconut Shell Stilts and Bamboo Stilts - Wahyono, Argo Adi; Harmono, Setyo; Junaidi, Slamet (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2021)
Stable body balance and leg muscle strength can be obtained with various exercises that should be given from the age of 0-6 years or the golden age where there is rapid growth and development process and the child begins to be sensitive to stimulation so that children's development must be optimized, for example through traditional stilt games. coconut shell. This study aims to determine the effect of body balance and leg muscle strength on the game of coconut shell stilts in class X SMA PGRI 1 Jombang. The research design used descriptive analysis. The population of this research is the students of class X SMA PGRI 1 Jombang which consists of 127 students. The sample used was 30 students who were taken using the random sampling technique. The dependent variable was body balance and leg muscle strength, while coconut shell stilts and bamboo stilts were independent variables. Statistical test using multiple linear regression test. The results of the research on the balance variable with a sample of 30 students of class X SMA PGRI 1 Jombang, obtained a mean of 71.5000 with a standard deviation of 13,14049, the highest score of 90 and the lowest score of 50. Based on the results of the calculation of multiple linear regression test the effect of body balance and muscle strength against the coconut shell stilt game, for the body balance variable, the t-count value is 3.595, while the t-table is 1.699 because t-count (3.595) > t-table (1.699). Variable leg muscle strength obtained t-count value of 3.561, while t-table of 1.699, because t-count (3.561) > t-table (1.699). The effect of body balance and muscle strength on bamboo stilts, variable leg muscle strength obtained t-count value of 3.250, while t-table of 1.699, because t-count (3.250) > t-table (1.699). The body balance variable obtained t-count value of 4.137, while t-table of 1.699, because t-count (4,137) > t-table (1,699). So it can be concluded that there is an effect of body balance and muscle strength on the game of coconut shell stilts and bamboo stilts in class X SMA PGRI 1 Jombang. Based on the conclusions of the research, it is suggested that further development and research should be carried out with a more in-depth study to increase the knowledge of the readers and it is hoped that the results of this research can be useful for lovers of traditional games.